2008
DOI: 10.1016/j.infbeh.2008.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in the responses of preterm infants to a painful stressor

Abstract: The purpose of this investigation was to examine longitudinally gestational age and developmental differences in preterm infants' self-regulatory abilities in response to a painful stressor, as well as associations between behavioral and cardiovascular responses. Participants included 49 healthy premature infants. Behavioral and cardiovascular responses to a heel stick blood draw were compared between infants of 28-31 and 32-34 weeks gestational age at birth. Both gestational age groups displayed behavioral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 57 publications
1
38
0
1
Order By: Relevance
“…By 24 weeks gestation, nociceptive circuitry for pain perception exists, but is not yet fully functional, such that painful stimuli appear to produce a more generalized response in preterm infants (Lucas-Thompson, Townsend et al 2008). Despite ongoing concerns about the impact of pain on the preterm brain, until very recently there have been relatively few studies directly linking pain and abnormal preterm brain development (recently reviewed in (Ranger and Grunau 2014)).…”
Section: What Extrinsic Injurious Events Interfere With Maturation?mentioning
confidence: 99%
“…By 24 weeks gestation, nociceptive circuitry for pain perception exists, but is not yet fully functional, such that painful stimuli appear to produce a more generalized response in preterm infants (Lucas-Thompson, Townsend et al 2008). Despite ongoing concerns about the impact of pain on the preterm brain, until very recently there have been relatively few studies directly linking pain and abnormal preterm brain development (recently reviewed in (Ranger and Grunau 2014)).…”
Section: What Extrinsic Injurious Events Interfere With Maturation?mentioning
confidence: 99%
“…Authors have shown that preterm NN pain evaluation and management need integral nursing care during procedures, regardless of complexity; in addition pain should be also appreciated as a vital sign of clinical importance. A study has evaluated 49 NN of different ages as to self-regulation abilities in response to painful stimuli and associations between behavioral and cardiovascular responses during heel puncture for blood collection 13 . Children aged 28-31 and 32-34 gestational weeks at birth were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their CNS immaturity, preterm infants may not reliably demonstrate behavioral responses to pain until after 30 weeks (Lucas-Thompson et al, 2008). Yet, behavioral indicators correlate with increases in HR and decreases in oxygen saturation in response to painful procedures (Holsti, Grunau, Oberlander, & Osiovich, 2008), suggesting that both physiologic and behavioral indicators contribute to pain assessment.…”
Section: Bigsbymentioning
confidence: 99%